IMPLEMENTASI AIDA PADA PENDAMPINGAN DIGITAL MARKETING UNTUK MENINGKATKAN OMSET PADA UMKM KABUPATEN SLEMAN - Siprianus, Febriana Lengi; Zaenal Wafa (Politeknik Negeri Sriwijaya, 2024)
Micro, Small and Medium Enterprises (MSMEs) are an important sector in the Indonesian economy. MSMEs are a sector consisting of small and medium scale businesses, both in terms of production, turnover and number of employees. They are often the backbone of the local economy, playing a role in creating jobs, supporting economic growth, and strengthening a country's economic resilience. The method used in this research is digital marketing assistance to increase turnover in Sleman Regency MSMEs. The result of this activity is to increase SMEs' understanding of digital marketing.